Planning and Organization in Waqf Management: Practice in Majlis Agama Islam dan Adat Istiadat Melayu Kelantan (MAIK) and Perbadanan Waqaf Negeri Sembilan (PWNS): Perancangan dan Pengorganisasian dalam Pengurusan Wakaf: Amalan Majlis Agama Islam dan Adat Istiadat Melayu Kelantan (MAIK) dan Perbadanan Wakaf Negeri Sembilan (PWNS) - Mat Daud, Mohamad Hilmie; Mubarak, Mohd Zain (Journal of Techno-Social, 2020)
Waqf institution has the potential and significant for improving the socio-economic and welfare of the ummah. In general, waqf management is seen as developing and capable of making an effective impact through waqf management agency Majlis Agama Islam Negeri (MAIN) in each state. This article focuses on waqf management through the application of management functions, particularly in the planning and organising aspects. A qualitative study using interviews and document study conducted on two state waqf management agencies, namely Majlis Agama Islam dan Adat Istiadat Melayu Kelantan (MAIK) and Perbadanan Wakaf Negeri Sembilan (WNS). The findings show that the planning and organising functions have been implemented by both agencies but still need to be further enhanced in terms of strategic plan formation, more structured work delegation, departmentation steps that cover various aspects and the formation of better organisational structures.